Installation of O‐Heterocycles to N‐Heteroarenes via an Et3B/O2‐Mediated Radical Reaction of α‐Alkoxy and α‐Alkoxyacyl Tellurides. Issue 7 (11th April 2019) - Kuwana, Daiki; Ovadia, Benjamin; Kamimura, Daigo; Nagatomo, Masanori; Inoue, Masayuki
Abstract: We report a radical‐based method that links highly oxygenated O‐heterocycles and N‐heteroarenes. Treatment of α‐alkoxy or α‐alkoxyacyl tellurides with Et3 B under air at room temperature generated α‐alkoxy carbon radicals, which were then added to protonated N‐heteroarenes. Regeneration of aromaticity proceeded in situ without an additional oxidant, leading to O‐heterocycle‐functionalized N‐heteroarenes. The present method enables the formation of hindered C(sp 3 )−C(sp 2 ) bonds between five O‐heterocycles and five N‐heteroarenes under mild conditions. Abstract : Gotta get these two connected : A radical‐based method that links highly oxygenated C(sp 3 )‐rich O‐heterocycles and N‐heteroarenes under mild conditions is reported herein. Treatment of α‐alkoxy or α‐alkoxyacyl tellurides with Et3 B under air at room temperature generated α‐alkoxy carbon radicals, which were then added to protonated N‐heteroarenes. Regeneration of aromaticity proceeded in situ without an additional oxidant, leading to various O‐heterocycle‐functionalized N‐heteroarenes.